OPTIMALISASI KOGNITIF LANSIA DENGAN DEMENSIA DI PSTW BANYUWANGI MELALUI TERAPI BUMA - Eky Madyaning Nastiti; Irwina Angelia Silvanasari; Nurul Maurida (LPPM Universitas dr. Soebandi, 2024)
Elderly experience various changes in body function, including cognitive function. The elderly at PSTW Banyuwangi showed signs of decreased memory abilities, which affected their ability to interact with other elderly people. Therefore, efforts need to be made to combine brain exercise and music therapy, called Terapi Buma (Brain Gym and Goyang Dumang Combination Therapy). The aim of this activity is to empower efforts aimed at preventing the decline in cognitive abilities in the elderly. The method used is in the form of a preparatory stage, including preparing the Buma Therapy Standart Operation Procedure (SOP), and data collection using the Mini Mental State Exam (MMSE) questionnaire. This program was done two times for a week with duration of 15 minutes each, by providing brain exercise and physical activity by following the music of the Goyang Dumang song. Combination of goyang dumang music and brain gyms has an effect on improving the average cognitive score. This brain exercise, combined with rocking dumang music therapy, can improve cognitive function. Listening to energetic music can increase the listener's spirit. Terapi BUMA can become a routine activity to be implemented for elderly people with dementia at PSTW Banyuwangi.